Religion as Context: Hellfire and Delinquency One More Time - Stark, Rodney (Sociology of religion, 1996)
More than 10 years ago the author proposed a contextual-interactional explanation of the fact that research done on the West Coast fails to find a relationship between religious commitment and delinquency, while studies done elsewhere invariably find a strong negative correlation. Unfortunately, because of various deficiencies, subsequent studies that claimed to test the contextual explanation have not done so — leaving the literature more confused than ever. In an effort to clarify matters, this paper carefully restates the contextual theory and then tests it on data from a very large survey of higfr school seniors. The results demonstrate the existence of a very potent contextual effect.